2017
DOI: 10.1111/ctr.12893
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus and quality of life in renal transplant patients

Abstract: The prevalence of pruritus markedly reduces after renal transplantation but remains substantially higher than in the general population and impacts upon quality of life in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
3
9
1
Order By: Relevance
“…Moreover, according to Altmeyer et al (25), both itch and histopathological changes disappeared completely after KTx. In comparison to Panuccio et al (9), we have reported a much lower itch prevalence (32% of RNRs). Nevertheless, it was still higher than in the healthy controls (11%).…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Moreover, according to Altmeyer et al (25), both itch and histopathological changes disappeared completely after KTx. In comparison to Panuccio et al (9), we have reported a much lower itch prevalence (32% of RNRs). Nevertheless, it was still higher than in the healthy controls (11%).…”
Section: Discussioncontrasting
confidence: 89%
“…Kidney transplant (KTx) is considered the best renal replacement therapy; however, its influence on itch was not sufficiently studied (8). The available data suggest that renal transplant recipients (RTR) may suffer from itch less frequently than patients treated with hemodialysis (9)(10)(11). Due to the insufficient reports and observations on small groups, we have decided to conduct a study and assess an actual prevalence of itch in RTR.…”
Section: Introductionmentioning
confidence: 99%
“…Following RTx, still no guarantee can be made on the disappearance of CKD-aI. Nevertheless, it bothers significantly lower fraction of adult patients than previously [ 26 , 27 , 28 ]. Based on our personal experience, children initially suffering from CKD-aI also benefit from RTx, with the majority of young recipients finally free from this symptom (unpublished data).…”
Section: Management Of Ckd-ai In Childrenmentioning
confidence: 98%
“…Based on recent data, it affects 42–44% of adults undergoing haemodialysis (HD) [ 22 , 23 ], while in patients undergoing peritoneal dialysis (PD) the percentages exceed 60% [ 24 , 25 ]. Patients who underwent successful renal transplantation (RTx) still complain of CI in up to 32% cases, albeit the percentages are lower than during their previous HD sessions [ 26 , 27 , 28 ]. However, CKD-aI may also bother CKD patients not yet on dialysis, including those with earlier stages of the disease [ 23 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pruritus also has a negative impact on quality of life (QoL) in dialysis patients. If pruritus was evaluated objectively using the Visual Analogue Scale (VAS), the Visual Rating Scale (VRS), and the Numerical Rating Scale (NRS), it was found that prevalence of pruritus markedly reduces after renal transplantation but remains substantially higher than in the general population and impacts upon quality of life in these patients [28].…”
Section: Quality Of Life Of Recipientsmentioning
confidence: 99%